Letter regarding cable transfer of £1987.1.8.
028-0220-001 The National City Bank of New York Incorporated with limited liability under the National Bank Act of the United States of America. 36, BISHOPSGATE, LONDON, E.C.2. 25th August, 1936. In accordance with cable/mail instructions received from our New York Office, and your letter 24th August, we hand you herewith our cheque for £1,987.1.8. Equivalent of $10,000.- at ex. 5.03¼ on account of... by order of Amalgamated Bank of New York. Kindly sign and return the attached receipt. To Mr. Walter Citrine, Transport House, Smith Square, LONDON, S.W.1. 292/946/28/220